Analisis Dampak Negatif Hukuman Fisik Oleh Orang Tua Terhadap Anak (6 - 12 Tahun) - manik, rachel; Apsari, Nurliana Cipta; Nurwati, Nunung (Politeknik Kesejahteraan Sosial Bandung, 2025)
Children aged 6 – 12 years are experiencing a new phase and need support from their families, especially their parents. Children will be very dependent on their parents because they are the people who have the closest relationship to the child. Therefore, parents must be able to motivate children and also provide support in facing new challenges in different environments. These challenges will certainly become new stressors for parents and children, as children will often make mistakes because they are still developing. Therefore, parents often apply physical punishment with the intention of correcting a child's behavior or mistakes. However, physical punishment applied by parents can have negative effects such as physical or mental injuries, and even damage to the relationship between parents and children. Even people who use physical punishment are often not aware that this method is considered child abuse behavior.Therefore, social workers have an important role in helping children as victims. Social workers can build trust with children through art therapy or play therapy. In this way, children realize that they are not alone and that not all adults have bad intentions so they can be trusted. Keywords: children, corporal punishment, parents, social workers